An elliptic problem with critical exponent and positive Hardy potential - Shaowei Chen; Shujie Li (Abstract and Applied Analysis)
We give the existence result and the vanishing order of the solution in 0 for the following equation: −Δu(x)+(μ/|x|2)u(x)=λu(x)+u2*−1(x), where x∈B1, μ>0, and the potential μ/|x|2−λ is positive in B1.